Dentomaxillofacial CBCT: Clinical Challenges for Indication-oriented Imaging - Wanderley, Victor Aquino; Vasconcelos, Karla de Faria; Leite, André Ferreira; Oliveira, Matheus L.; Jacobs, Reinhilde (Seminars in Musculoskeletal Radiology, 2020)
This critical review discusses the clinical challenges for patient-specific and indication-oriented dentomaxillofacial cone beam computed tomography (CBCT). Large variations among units and protocols may lead to variable degrees of diagnostic and three-dimensional model accuracy, impacting both specific diagnostic tasks and treatment planning. Particular indications, whether diagnostic or therapeutic, may give rise to very specific challenges with regard to CBCT unit and parameter setup, considering the required image quality, segmentation accuracy, and artifact level. Considering that dental materials are in the field of view needed for diagnosis or treatment planning, artifact expression is a dominant factor in proper CBCT selection. The heterogeneity of dental CBCT units and performances may highly impact the scientific results. Thus research findings cannot be simply generalized as published evidence, and a demonstrated clinical applicability for a specific indication should not be simply extrapolated from one CBCT unit to another.
Keywords: image quality; cone beam computed tomography; metal artifacts; dentomaxillofacial radiology